HYPOGLYCAEMIC AND BIOCHEMICAL PROPERTIES OF CNESTIS FERRUGINEA - Adisa, R. A.; Choudhary, M. I.; Adewoye, E. O.; Olorunsogo, O. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Increasing incidences of diabetes in Africa has prompted the search for safe and readily available alternative herbal remedies for the treatment of diabetes mellitus. Cnestis ferruginea was extracted with methanol and ethylacetate and the extracts obtained were tested for hypoglycaemic activities in streptozotocin (STZ)–induced diabetic rats and mice. The extracts (250mg/kg body weight) were administered orally for 10 consecutive days to STZ-induced diabetic rats while a single dose (250mg/kg body weight) of the extracts were administered to STZ-induced diabetic mice. Fasting blood glucose (FBG) levels were determined in the two groups of animals after extract administration. There was significant reduction in FBG (P< 0.005) by MCF and ECF within 4 hrs of extract administration in a time- dependent manner. Furthermore, administration of MCF and ECF for 10 days significantly lowered FBG in STZ diabetic rats (P<0.005) by 74% and 68%, respectively, whereas, glibenclamide - a standard antidiabetic drug reduced FBG by 60%. The levels of serum creatinine, urea, triglyceride, total cholesterol, total protein and level of lipid peroxidation were also evaluated. The extracts reduced significantly (P<0.005) the elevated levels of serum ALT and AST in diabetic treated rats. Similarly, both extracts significantly lowered (P<0.005) the levels of serum creatinine, urea, total cholesterol, triglyceride and thiobarbituric acid reactive species (TBARS). These results suggest that Cnestis ferruginea leaves contain a highly potent hypoglycaemic principle and could be a potential source for isolation of new orally active antihyperglycaemic compounds for attenuating secondary complications of diabetes such as atherosclerosis, liver and renal dysfunction.